Exploring Life Experiences through Literature Circles - Johana Mendez Sarmiento; Carolina Piñeros Pedraza (Asociación Colombiana de Profesores de Ingles, 2016)
This article informs on some insights about pupils' reading engagements through literature circles and the way those circles can be implemented in the classrooms. Such practices are based upon students' life experiences in order to construct new understanding about life itself as well as to foster reflection, providing students with the opportunity of playing an active role in their language learning decision-making.